Association of transport time with adverse outcome in paediatric trauma. Issue 3 (8th April 2021) - Träff, Helen; Hagander, Lars; Salö, Martin
Abstract: Background: It is unclear how the length of prehospital transport time affects outcome in paediatric trauma. This study evaluated the association of transport time from alarm to arrival at hospital with adverse outcome in paediatric trauma patients in Sweden. Methods: This was a retrospective study based on prospectively collected data from the Swedish trauma registry between 2012 and 2019 of children less than 18 years with major trauma (New Injury Severity Score (NISS) greater than 15). The primary outcome was 30-day mortality, and secondary outcomes were emergency interventions (e.g., chest tube or laparotomy) and low functional outcome (Glasgow Outcome Scale 2–3). Primary exposure was transport time from alarm to arrival at hospital. Co-variables in multivariable regressions were gender, age, ASA score before injury, injury intention, dominant injury type, NISS, Glasgow Coma Scale score, prehospital competence and hospital level. Results: Among 597 patients, 30-day mortality was 9.8 per cent, emergency interventions were performed in 34.7 per cent and low functional outcome was registered in 15.9 per cent. Median transport time was 51 (i.q.r. 37–68) minutes. After adjustment for patient, injury and hospital characteristics, no association between longer transport time and 30-day mortality, frequency of emergency interventions or lower functional outcome could be found. Treatment at a university hospital was associated with a lower risk for 30-day mortality (odds ratio 0.23 (95 per cent c.i. 0.08 to 0.68), P  = 0.008). Conclusion: Longer transport time after major paediatric trauma was not associated with adverse outcome. Hence, it seems that longer transport distances should not be an obstacle against centralization of paediatric trauma care. Further studies should focus on the role of prehospital competence and other transport-associated parameters and their association with adverse outcome. Abstract : The aim of the study was to evaluate the association of transport time with adverse outcome in pediatric trauma patients in Sweden, using a prospective trauma registry including children with major trauma. The median transport time from alarm to hospital was 51 minutes, and among 597 patients 30-day mortality was 10%, emergency interventions were performed in 35% and low functional outcome was registered in 16%. After adjustment for possible covariates, the results showed that longer transport time after major pediatric trauma was not associated with a higher 30-day mortality, a higher rate of emergency interventions or lower functional outcome.